Hydrogen-enhanced fatigue life analysis of Cr–Mo steel high-pressure vessels. (20th April 2017) - Hua, Zhengli; Zhang, Xin; Zheng, Jinyang; Gu, Chaohua; Cui, Tiancheng; Zhao, Yongzhi; Peng, Wenzhu
Abstract: Cr–Mo steel high-pressure vessel made of 4130X is a promising economical candidate for hydrogen storage and transport in hydrogen refueling stations. However, the mechanical properties of 4130X in hydrogen gas and the hydrogen-enhanced fatigue life of a 4130X vessel with a design pressure higher than 45 MPa are not completely understood. In this work, the tensile and fatigue properties of 4130X at different positions of a manufactured vessel in 92 MPa hydrogen gas were studied. The fatigue life prediction for the 4130X vessel was performed using fracture mechanics method. The influences of initial crack size and outside diameter on the fatigue life were also investigated. Results indicate that the 4130X from the shoulder area attains a lower relative reduction of area (RRA) and higher fatigue-crack growth rate (FCGR) in hydrogen gas than those of the specimens from the cylinder and juncture. The FCGR measured in hydrogen increases with increasing hydrogen pressure, and the FCGR in 92 MPa hydrogen gas is 30–50 times of the FCGR in air. As the initial crack size increases, not only the fatigue life of the hydrogen storage vessel decreases, but also the hydrogen-induced fatigue life loss is aggravated. Furthermore, the influence of outside diameter on the fatigue life of the hydrogen storage vessel is minimal. Highlights: The mechanical properties of 4130X from different positions of a manufactured vessel in 92 MPa hydrogen gas were tested. The fatigue life prediction for the 4130X vessel was performed based on fracture mechanics method. The influences of the initial crack size and outside diameter on the fatigue life of the 4130X vessel were studied.